2016
DOI: 10.3389/fncir.2016.00092
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Vasopressinergic Projections Innervate Central Amygdala GABAergic Neurons: Implications for Anxiety and Stress Coping

Abstract: The arginine-vasopressin (AVP)-containing hypothalamic magnocellular neurosecretory neurons (VPMNNs) are known for their role in hydro-electrolytic balance control via their projections to the neurohypophysis. Recently, projections from these same neurons to hippocampus, habenula and other brain regions in which vasopressin infusion modulates contingent social and emotionally-affected behaviors, have been reported. Here, we present evidence that VPMNN collaterals also project to the amygdaloid complex, and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 43 publications
3
97
0
Order By: Relevance
“…We have previously reported that, in the hippocampus and amygdala, there are two types of AVP‐immunopositive fibres: thick ones (with an average thickness of 700‐1000 nm) and thin ones (with an average thickness of 200‐500 nm), distributed and intermingled in selective subfields, with both selectively establishing Gray I and Gray type II synapses preferentially at pyramidal neurones and interneurones, respectively . In the present study, we report an additional observation of a third type that made excitatory synapses onto unidentified hippocampal cellular segments.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…We have previously reported that, in the hippocampus and amygdala, there are two types of AVP‐immunopositive fibres: thick ones (with an average thickness of 700‐1000 nm) and thin ones (with an average thickness of 200‐500 nm), distributed and intermingled in selective subfields, with both selectively establishing Gray I and Gray type II synapses preferentially at pyramidal neurones and interneurones, respectively . In the present study, we report an additional observation of a third type that made excitatory synapses onto unidentified hippocampal cellular segments.…”
Section: Resultsmentioning
confidence: 54%
“…The origin of vasopressin (AVP)‐containing afferents to given limbic regions, including the hippocampus, has been the subject of detailed recent investigations. AVP‐magnocellular neurones of the hypothalamus provide glutamatergic projections to the hippocampus, amygdala, lateral habenula and locus coeruleus . However, we have also reported AVP‐immunopositive fibres in those regions, which are much thinner and make Gray type II synapses.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…Acute withdrawal (3 hours and 1 day) after chronic “binge” treatment with cocaine (3 × 15 mg kg ‐1 day ‐1 for 14 days) produced an increase in amygdala AVP mRNA levels; however, this increase did not persist after 10 days of withdrawal . This shows that the effects of cocaine on anxiety‐like behaviours could be the result of an increased anxiety response induced by AVP release in the amygdala …”
Section: Psychostimulants and Vasopressinmentioning
confidence: 96%
“…Vasopressin expression may increase following neglect or other negative social experiences in early life (Hernandez et al, 2016;Murgatroyd et al, 2009). We hypothesize that early adversity could also upregulate the vasopressin receptor, especially in brain regions necessary to allow mobilized responses in later life and possibly affecting the capacity to form attachments.…”
Section: Early Life Experiences Influence the Capacity For Subsequentmentioning
confidence: 98%